Cytotype regulation of P transposable elements in Drosophila melanogaster: repressor polypeptides or piRNAs? - Jensen, P.A.; Stuart, J.R.; Goodpaster, M.P.; Goodman, J.W.; Simmons, M.J. (Genetics, 2008)
The telomeric P elements TP5 and TP6 are associated with the P cytotype, a maternally inherited condition that represses P-element-induced hybrid dysgenesis in the Drosophila germ line. To see if cytotype repression by TP5 and TP6 might be mediated by the polypeptides they could encode, hobo transgenes carrying these elements were tested for expression of mRNA in the female germ line and for repression of hybrid dysgenesis. The TP5 and TP6 transgenes expressed more germ-line mRNA than the native telomeric P elements, but they were decidedly inferior to the native elements in their ability to repress hybrid dysgenesis. These paradoxical results are inconsistent with the repressor polypeptide model of cytotype. An alternative model based on the destruction of P transposase mRNA by Piwi-interacting (pi) RNAs was supported by finding reduced P mRNA levels in flies that carried the native telomeric P elements, which are inserted in a known major piRNA locus.